Studies on Homalomeneae (Araceae) of Sumatera V : Homalomena squamis-draconis, a new species for the Chamaecladon Clade - Boyce, P.C; Wong, Sin Yeng (International Aroid Society, Inc., 2016)
Homalomena squamis-draconis, a highly ornamental new dwarf species of Chamaecladon clade, is described and illustrated from Sumatera.